Central Nervous System Plasticity Influences Language and Cognitive Recovery in Adult Glioma. Issue 4 (20th January 2021) - Krishna, Saritha; Kakaizada, Sofia; Almeida, Nyle; Brang, David; Hervey-Jumper, Shawn
Abstract: Gliomas exist within the framework of complex neuronal circuitry in which network dynamics influence both tumor biology and cognition. The generalized impairment of cognition or loss of language function is a common occurrence for glioma patients. The interface between intrinsic brain tumors such as gliomas and functional cognitive networks are poorly understood. The ability to communicate effectively is critically important for receiving oncological therapies and maintaining a high quality of life. Although the propensity of gliomas to infiltrate cortical and subcortical structures and disrupt key anatomic language pathways is well documented, there is new evidence offering insight into the network and cellular mechanisms underpinning glioma-related aphasia and aphasia recovery. In this review, we will outline the current understanding of the mechanisms of cognitive dysfunction and recovery, using aphasia as an illustrative model.